2013
DOI: 10.1007/s00784-013-1003-6
|View full text |Cite
|
Sign up to set email alerts
|

Two-year results of vital pulp therapy in permanent molars with irreversible pulpitis: an ongoing multicenter randomized clinical trial

Abstract: Vital pulp therapy with CEM is a cost-effective and reliable biological technique for endodontic treatment of permanent molar teeth with irreversible pulpitis and can be recommended for general clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 55 publications
3
110
0
Order By: Relevance
“…Finally, 31 articles were included: 15 case reports or case series (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), 9 cohort studies (15,(31)(32)(33)(34)(35)(36)(37)(38), and 3 clinical trials and 4 randomized clinical trials (39)(40)(41)(42)(43)(44)(45).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 31 articles were included: 15 case reports or case series (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), 9 cohort studies (15,(31)(32)(33)(34)(35)(36)(37)(38), and 3 clinical trials and 4 randomized clinical trials (39)(40)(41)(42)(43)(44)(45).…”
Section: Methodsmentioning
confidence: 99%
“…The third group of publications gathered follow-up studies aiming to verify whether pulpotomy could be an alternative to RCT in a public health perspective (15,(34)(35)(36)(37)(38)(42)(43)(44)(45).…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Several factors related to endodontic technique can result in the need for a new intervention of endodontically treated teeth, including the ability and knowledge of the professional who performed the primary endodontic treatment. Epidemiological studies have shown a higher percentage of failure [20,21] when the root canal therapy is performed by general clinicians, when compared to treatments that were performed by specialists, which have a success rate of up to 94% [2]. Moreover, the quality of coronal restorations can also contribute to failure of endodontic therapy [16], which is in accordance with the findings of the present study, where the failure or fracture of coronal restoration retained by composite resin, amalgam, prosthetic crown, or provisional material represented a significant percentage of cases that were indicated for new root canal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…When irreversible pulpitis is clinically diagnosed, the common school of thought recommends removal of entire vital pulp, despite containing competent stem cells with proliferative potential [ 121 ]. In the light of recent evidences and in order to gain a better understanding of pulp healing capability, the infl ammatory process and pathogenesis of the dental pulp need to be reconsidered, particularly in cases of irreversible pulpitis [ 14 ]; such a modern approach can lead to preservation of the dental pulp in mature permanent teeth and, thus by healing of the diseased pulp, can have a positive impact on improving the tooth survival rate as well as patients' quality of life. Current dental educational system defends the correlation between spontaneous pain or lingering pain in response to cold stimuli and the existence of irreversible pulpitis that necessitates the complex/expensive process of root canal therapy.…”
Section: Commentsmentioning
confidence: 98%